ALTERNATIF PILIHAN INPUT TEKNOLOGI, INVESTASI ATAUKAH TENAGA KERJA DALAM PENGEMBANGAN USAHA KECIL DAN MENENGAH PASAR EKSPOR - B Heatubun, Adolf; Gamot Malau, Albert (LPPM Universitas Terbuka, 2009)
The objective of the study was to analyze the factors have influenced the increasing of investment, technology improvement, labor absorption, production and export of the exporting small and medium enterprises. An econometric model using simultaneous equations of the economic sectoral pooled data has resulted that the technology of exporting small and medium enterprises was weakness, so that the government could to improve the technology by improving human capital and by expanding its expenditures.